Wall motion score index and left ventricular ejection fraction as predictors of cardiovascular events after acute myocardial infarction - Venkateshwaran, R.; Arumugam, M. A. (International Journal of Advances in Medicine, 2023)
Background: Left ventricular ejection fraction serves as a vital gauge of left ventricular overall function and plays a crucial role in assessing the severity and prognosis of ischemic heart disease. Another approach for evaluating left ventricular function is through the assessment of regional function using the wall motion score index. In this study, our objective was to assess and compare the predictive value of both WMSI and LVEF in patients with Acute Myocardial Infarction for their ability to predict all-cause mortality and readmission due to heart failure. Methods: This prospective study was conducted on admitted patients in Government Kilpauk Medical College on 70 patients with Acute myocardial infarction between the first 48 hours of symptoms and before hospital discharge. Follow-up with clinic visits was conducted 3, 6 and 12 months after discharge. The primary endpoint was the composite of all-cause mortality and readmission for heart failure. Results: 63% of patients had LVEF of less than 40%, and 55% had WMSI>1.5. After a follow-up of 1 year, 3.7% mortality and 11% readmission for heart failure were observed. WMSI>1.5 and LVEF<40% were associated with poor survival, while the WMSI proved to be a better predictor for rehospitalisation. 81% of STEMI group patients had EF<40%, but only 18% of the NSTEMI group had EF < 40%, which is statistically significant. There is no superiority between WMSI and LVEF in the STEMI and NSTEMI groups. Killip classification proved to be an independent predictor of mortality, but no statistical significance was observed in readmission. Conclusions: Both LVEF and WMSI were predictors of all-cause mortality, while the WMSI was a predictor for readmission for heart failure.